Effect of raw and processed cowpea on growth and heamatological profile of broiler chicken - Akanji, AM; Fasina, OE; Ogungbesan, AM (Bangladesh Journal of Animal Science, 2016)
A study was carried out to look at the utilization of cowpea based diets on performance characteristics and haematology of broiler chickens. Raw cowpea, dehulled cowpea, dehulled cooked cowpea and dehulled roasted cowpea grains were fed to broiler chickens in an eight week feeding trial. A total of two hundred (200) day old unsexed broiler chicks of Marshall strain were allotted into five dietary treatments.?Feed intake and growth were significantly (P < 0.05) reduced in birds fed raw cowpea and dehulled cowpea respectively. The feed conversion efficiency (FCE) and protein efficiency ratio (PER) also followed a similar pattern. Non significant (P > 0.05) differences were however obtained in weight gain, FCE and PER of birds fed control diet and those fed dehulled cooked cowpea in this study. Birds fed dehulled roasted cowpea also had marginal reductions in weight gain, FCE and PER when compared to those fed dehulled cooked cowpea based diet. The haematological studies showed lower (P < 0.05) values of haemoglobin, red blood cells, packed cell volume and white blood cells of birds fed raw cowpea and dehulled cowpea respectively. The best significant indices in this study were however obtained in birds fed dehulled cooked cowpea. Bang. J. Anim. Sci. 2016. 45 (1): 62-68